The relationship among restless legs syndrome (Willis–Ekbom Disease), hypertension, cardiovascular disease, and cerebrovascular disease - Ferini-Strambi, Luigi (Springer Berlin Heidelberg, 2013)
Untreated sleep disorders may contribute to secondary causes of uncontrolled hypertension, cardiovascular disease (CVD), and stroke. Restless legs syndrome, or Willis–Ekbom Disease (RLS/WED), is a common sensorimotor disorder with a circadian rhythmicity defined by an uncontrollable urge to move the legs that worsens during periods of inactivity or at rest in the evening, often resulting in sleep disruptions. Sleep disorders such as insomnia and obstructive sleep apnea (OSA) are established risk factors for increased risk of hypertension and vascular diseases. This literature review outlines the lessons learned from studies demonstrating insomnia and OSA as risk factors for hypertension and vascular diseases to support the epidemiologic and physiologic evidence suggesting a similar increase in hypertension and vascular disease risk due to RLS. Understanding the relationships between RLS and hypertension, CVD, and stroke has important implications for reducing the risks associated with these diseases.